2015
DOI: 10.1039/c5cs00279f
|View full text |Cite
|
Sign up to set email alerts
|

Materials for suspension (semi-solid) electrodes for energy and water technologies

Abstract: Suspension or semi-solid electrodes have recently gained increased attention for large-scale applications such as grid energy storage, capacitive water deionization, and wastewater treatment. A suspension electrode is a multiphase material system comprised of an active (charge storing) material suspended in ionic solution (electrolyte). Gravimetrically, the electrolyte is the majority component and aids in physical transport of the active material. This principle enables, for the first time, scalability of ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(128 citation statements)
references
References 148 publications
(341 reference statements)
2
125
1
Order By: Relevance
“…27,148,208 Second, four suspension storage tanks are needed for intermittent flow operation because one tank is required for charged suspensions and one for discharged suspensions for each electrode. 104 Such a system must then account for the additional cost, space, and complexity requirements of four tanks as opposed to two per system. In addition, a stable method to switch active material batches is needed to avoid power interruptions between batches of electrolyte suspension being pumped into the electrochemical reaction cell intermittently.…”
Section: Flow and Agitation Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…27,148,208 Second, four suspension storage tanks are needed for intermittent flow operation because one tank is required for charged suspensions and one for discharged suspensions for each electrode. 104 Such a system must then account for the additional cost, space, and complexity requirements of four tanks as opposed to two per system. In addition, a stable method to switch active material batches is needed to avoid power interruptions between batches of electrolyte suspension being pumped into the electrochemical reaction cell intermittently.…”
Section: Flow and Agitation Methodsmentioning
confidence: 99%
“…More details and discussions on capacitive water deionization and electrochemical flow electrodes can be found in recent reviews. 104,106,108,[111][112][113] Research on electrochemical flow capacitors and water capacitive deionization has demonstrated the applicability of solid suspensions for capacitive and electrochemical devices. Recently, progress has also been made in using solid suspensions in RFBs-where the move to solid particles provides a route to increase the battery energy density by overcoming the solubility limitation of active species.…”
Section: Solid Suspensions For Capacitive and Electrochemical Applmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with the idea that electrochemical capacitor power density can be significantly enhanced with the introduction of redox-active electrolytes, the possibility of creating flow capacitors (Hatzell et al, 2015) has emerged.…”
Section: Increase Of the Pseudocapacitancementioning
confidence: 99%